Integration of Woody Perennials in Production Systems to Augment Feed Availability in Hot Arid Region: A Review - Singh, J.P.; Rathore, V.S. (Annals of Arid Zone, 2023)
Livestock is the mainstay of agrarian economy of the hot arid region. However,shortage of fodder and feed is one of the main constraints of animal production inthe region. Trees and shrubs are indispensable sources of animal feed in arid region.They can alleviate the feed shortages or even fill up the feed gaps in the winter andespecially in the summer period when grassland growth is limited or dormant, due tounfavorable weather conditions. Destruction of natural habitats, over exploitation andincreased mechanization in agriculture during the concluding couple of decades resultedin a precipitous fall in the number and diversity of woody perennials in cultivated andother lands. There is an urgent need to conserve and sustainable utilization of foddertree and shrubs to augment feed availability in hot arid region. In this paper an attempthas been made to review the significance and nutritional quality of tree and shrubs forlivestock. The integration of trees and shrubs in agricultural and pasture productionsystems is explored. The important constraints for their utilization and need for researchand development are discussed